PENGARUH TEMPERATUR SISTEM PADA FIGURE OF MERIT STASIUN BUMI PITA S DAN PITA X - Surjo, Achmadi (BRIN Publishing, 2004)
One of the veri important in a satellite communications system is the figure of merit for space segment as well as for the ground segment. The parameter which will be discussed in this paper is the figure of merit of a ground station of S band and X band for remote sensing system application. The parameters which influences it are antenna gain and temperature of system. The antenna which will be used is parabola antenna whose magnitude gain depends on diamter and efficiency of reflector. While the ground station antenna moves to track the desired satellite, so the elevation angle changes as well as the azimuth angle. On S band system influence of rain cab be ignored, while on the X band the influence needs to be considered. From the analysis conducted at 0.1 time percentage, the result is influence of rain to the